Autobiographical memory in children with Idiopathic Generalised Epilepsy. (January 2015) - Gascoigne, Michael B.; Barton, Belinda; Webster, Richard; Gill, Deepak; Lah, Suncica
Abstract: Autobiographical memory involves the recall of both personal facts (semantic memory) and the re-experiencing of past personal events (episodic memory). The recall of autobiographical episodic details has been associated with a specific network, which involves the prefrontal and medial temporal lobes, in addition to posterior regions of the brain. Seizure activity has been previously shown to disrupt the consolidation of newly-learned information into long-term memory, but it is not yet known whether primary generalised seizures alone are also associated with deficits in the recall of autobiographical memories. Here we examined this recall in children who experience generalised rather than localisation-related seizures: children with Idiopathic Generalised Epilepsy (IGE). In this study, 18 children with IGE and 42 healthy controls of comparable age (6–16 years), sex and socio-economic status were administered the Children's Autobiographical Interview (CAI). Compared with controls, children with IGE recalled significantly fewer episodic details, even when retrieval prompts were provided. In contrast, no group difference was found for the recall of semantic autobiographic details. Within the IGE group, hierarchical regression analyses showed that patient age and earlier age of diagnosis were significantly related to the recall of episodic autobiographical details over different conditions of the CAI, explaining up to 37% of variance. To our knowledge, this study provides the first evidence of autobiographical episodic memory deficits in patients with primary generalised seizures. As no evidence of localisation-related epilepsy is apparent in patients with IGE, our findings suggest that generalised seizures alone, especially when developed at an early age, could compromise memories for personally-experienced events. Highlights: For the first time, autobiographical memory deficits are shown in children with IGE. Children with IGE recalled fewer episodic, but not semantic, details than controls. Episodic deficits were evident despite the provision of directed retrieval support. Earlier onset of IGE was associated with poorer episodic recall.